COMPARATIVE STUDY OF MATHIEU AND SNODGRASS REPAIR FOR ANTERIOR HYPOSPADIAS - Haq, Anwar -ul-; Akhter, Nadeem; Nilofer, Nilofer; ullah, Sami; Javeria, Javeria (Journal of Ayub Medical College Abbottabad, 2006)
Background: This study was carried out to compare the operative time and rate of complications of Mathieu and Snodgrass procedures for the repair of primary anterior hypospadias. Methods: This study was carried out in the Department of Pediatric Surgery, The Children hospital, Pakistan Institute of Medical Sciences Islamabad, from March 2003 to Feb 2005. We managed 90 patients with primary anterior hypospadias. Children between 2 years to 12 years were included in the study. Those who had previous repair were excluded from the study. Only those patients were selected who never had their hypospadias repaired. Those with significant chordee were also excluded from the study. Patients were divided into two groups. Group I had Mathieu repair and Group II had Tubularized Incised Plate (TIP) urethroplasty (Snodgrass procedure). Stent was kept patent by frequent irrigation. Operative time was calculated for both the procedures separately. Patients were followed for subsequent complications. Results: A total of 90 cases were studied. Mathieu repair was performed in 45 patients and tubularized incised plate (TIP) urethroplasty (Snodgrass procedure) in the rest of 45 patients. Cosmetic results were excellent with Snodgrass repair with a normal looking slit like meatus. Meatal stenosis and wound breakdown was equal in each group whereas urocutaneous fistula and proximal urethral stricture were seen more frequently in Mathieu group. Keywords: Anterior hypospadias, Mathieu repair, Tubularized Incised Plate urethroplasty (TIP), Snodgrass procedure